Analisis Investasi Saham Sektor Energi Menggunakan Metode Value at Risk (VAR) dan Conditional Value at Risk (CVAR) dengan Pendekatan Single Index Model: Studi Kasus Indeks LQ45 Tahun 2025 - Ayu Nor Aisah; Eka Krisna Santoso; Nurul Maqfirah Rauf (Journal of Economic and Business Advancement, 2026)
The energy sector is characterized by high volatility, making comprehensive risk analysis essential for investment decision-making. This study examines the risk and return characteristics of energy sector stocks included in the LQ45 index in 2025 by integrating the Single Index Model with Value at Risk (VaR) and Conditional Value at Risk (CVaR). Daily closing price data from February 2022 to July 2025 are employed to estimate stock returns, market sensitivity, and portfolio risk. The Single Index Model identifies three optimal stocks AKRA, MEDC, and PGAS based on their Excess Return to Beta and positive Zᵢ values, resulting in portfolio weights of 39.6%, 51.8%, and 8.5%, respectively. Monte Carlo simulation is applied to estimate portfolio risk at a 95% confidence level. The results indicate that the portfolio’s VaR reflects a manageable level of potential daily loss, while the CVaR reveals the average loss under extreme market conditions beyond the VaR threshold. Overall, the findings suggest that the optimal energy sector portfolio offers a balanced risk–return profile with controlled exposure to market and tail risks, providing valuable insights for risk-aware investors.